The ecology of reintroduced lions on the Welgevonden Private Game Reserve, Waterberg - Kilian, Petrus Johannes (2013)
Five lions were reintroduced to the Welgevonden Private Game Reserve in 1998. These lions were studied to increase the limited knowledge of the ecology of reintroduced lions on small wildlife reserves, and to provide baseline data to the reserve management from which to develop management decisions. In the past, reintroduction attempts of felids have often failed because the animals failed to establish ranges in the new environment. During the current study, homing behaviour and range establishment of the reintroduced lions were studied and used as an indication of the success of the reintroduction attempt. The ease with which lions on Welgevonden established ranges indicated that they did not experience problems with adapting to their new environment The population dynamics of the reintroduced lion population were investigated. The population grew rapidly due to early breeding and short inter-litter intervals. The collected data were used to model the lion population using VORTEX population modelling software. Various potential management strategies to reduce the population growth were also modelled and discussed. The feeding ecology and predation patterns of the reintroduced lions• were investigated to give an indication of the predator-prey relationships on Welgevonden. These data were used in a model that investigated the effect of lion predation on the various prey populations of Welgevonden. The model was also used to test the influence of other factors on the prey populations, as well as the number of killing lions that can be supported by the prey population. The study has shown that reintroduction can be used successfully to establish a lion population on a small game reserve, but that certain management actions will increase the chances of success. However, continual monitoring and management will be necessary to ensure the long-term viability of the lion and prey populations. <p. === Dissertation (MSc (Wildlife Management))--University of Pretoria, 2006. === Centre for Wildlife Management === unrestricted